2017
DOI: 10.1177/0300985816688754
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Histopathologic Characterization of Canine Chronic Ulcerative Stomatitis

Abstract: Canine chronic ulcerative stomatitis, also known as chronic ulcerative paradental stomatitis, is a painful condition of the oral cavity. The purpose of this study was to determine if there are commonalities in clinical and radiographic features among patients, whether the histopathologic evaluation might inform the pathogenesis, and whether the condition appears similar to human oral mucosal diseases. To do this, we prospectively collected clinical, radiographic, and histopathologic data from 20 dogs diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 56 publications
1
25
0
1
Order By: Relevance
“…We have previously described the clinical, radiographic, clinicopathologic and histopathologic characteristics of this disease. [1] We have further provided a preliminary and qualitative characterization of the inflammatory cell infiltrate that characterizes CCUS lesions. Specifically, we showed that CCUS lesions are rich in both B and T lymphocytes, as well as IL-17 producing cells.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously described the clinical, radiographic, clinicopathologic and histopathologic characteristics of this disease. [1] We have further provided a preliminary and qualitative characterization of the inflammatory cell infiltrate that characterizes CCUS lesions. Specifically, we showed that CCUS lesions are rich in both B and T lymphocytes, as well as IL-17 producing cells.…”
Section: Introductionmentioning
confidence: 99%
“…We have introduced a clinical scoring system, called the Canine Ulcerative Stomatitis Disease Activity Index (CUSDAI) in an attempt to quantify disease severity and response to various therapeutic regimens "S1 Table". [1] CCUS histopathology typically features a densely arrayed inflammatory cell infiltrate at the interface between the superficial mucosal epithelium and subepithelial connective tissue (lichenoid infiltrate) that is composed of B cells, plasma cells, CD3 T cell subsets (including FoxP3+), neutrophils, and fewer mast cells within the deep submucosa. [1] An initial evaluation using multi-color immunofluorescence (IF) on a small number of CCUS cases, revealed moderate numbers of infiltrating IL17 + cells; interestingly the majority of these cells were determined to be CD3 negative.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations